BIOMETRIC FACE IMAGE PRIVACY USING VISUAL CRYPTOGRAPHY - MS. PAWAR SARIKA D.; PROF.PAWAR D.B. (International Journal of Innovations in Engineering Research and Technology, 2021)
Visual cryptography is cryptographic methodallowing data to be stored in encrypted format were any individual can decrypt such data by sight readingof human if accurate key imagesare used. Biometricdeals with automatic identification of any individual based on physical or behavioralcharacteristics of individual.Preserving privacy in biometric data such as face images which are stored in central database are important.The paperdeals with the work based on visual cryptography to provide privacy to biometric data such as iris codes, fingerprint images and face images.Visual cryptographyis a method in which a private image is encrypted intothe sheetswhich are incapable of revealing information about original private image,if used independently. Biometric informationare stored in thecentralized databaseand are vulnerable to attacks which can modify original content and authorized owner may not be able to access the resource.Totackle this issue visual cryptography schemes can be applied tosecure privacy of digital biometric information. In this method the private image or face is dithered in to two different host images i.e., sheetsand are stored in separate data serversso as to ensure that the original image can get retrievedonly by accessing both sheets together at a time and single sheet will not be able to reveal any information of private image